Treatment of recurrent epithelial ovarian carcinoma with single-agent apatinib - Huang, Yaqing; Xu, Yun; Li, Xiaodong; Rui, Xiaohui; Jiang, Xiping; Zhang, Fenghua; Jiang, Jingting (Translational Cancer Research; Vol 6, No 1 (February 27, 2017): Translational Cancer Research (Focused Issue: Advances on Clinical Immunotherapy), 2017)
A 59-year-old woman was admitted and diagnosed as epithelial ovarian cancer. Postoperative pathological exam confirmed papillary adenocarcinoma. Then the patient received six cycles of chemotherapy with the regimen of paclitaxel plus nedaplatin. Two months after the last cycle, the recurrence of disease was revealed. Based on the gene detection revealing high expression of VEGF and low expression of RRM1, apatinib mesylate tablet was administered at a dose of 250 mg twice a day. During the administration of apatinib only manageable side effects occurred. About 8 months later a PET/CT scan suggested a partial remission of disease.